View and visits of articles on neglected tropical diseases in the Malaysian Medical Gazette (MMG) website - Abdul Rashid, Aneesa; Ismawi, Hidayatul Radziah (2019)
We aim to determine the number of views and Entries1 (first page that is directly linked to) of articles on NTDs in the MMG from July 2018 until June 2019.